2021
DOI: 10.1021/acsaelm.1c01102
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Ion-Cutting of β-Ga2O3 and Wafer-Scale Heterogeneous Integration of a β-Ga2O3 Thin Film onto a Highly Thermal Conductive SiC Substrate

Abstract: Heterogeneous integration of a β-Ga2O3 thin film with a highly thermal conductive substrate by the ion-cutting process is an intelligent technology to overcome the poor-nature thermal conductivity of β-Ga2O3 and to unleash the full potential of β-Ga2O3 in the field of power electronics. Understanding the basic mechanism of the implantation-induced exfoliation behavior of β-Ga2O3 is vital for better application of the ion-cutting technology. In this work, the thermodynamics of β-Ga2O3 surface blistering induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Xu et al reported the wafer-scale exfoliation of β-Ga 2 O 3 thin films by an ioncutting technique with H implantation and transfer onto 4H-SiC and Si substrates with high thermal conductivity. This avoids causing poor quality of the hetero-epitaxy-grown film due to the large lattice mismatch [141][142][143][144][145]. Compared to bulk Ga 2 O 3 wafer, it demonstrated a fine performance improvement in leakage current and breakdown voltage and better thermal stability.…”
Section: Contact Interface Of Metal/ga 2 Omentioning
confidence: 99%
“…Xu et al reported the wafer-scale exfoliation of β-Ga 2 O 3 thin films by an ioncutting technique with H implantation and transfer onto 4H-SiC and Si substrates with high thermal conductivity. This avoids causing poor quality of the hetero-epitaxy-grown film due to the large lattice mismatch [141][142][143][144][145]. Compared to bulk Ga 2 O 3 wafer, it demonstrated a fine performance improvement in leakage current and breakdown voltage and better thermal stability.…”
Section: Contact Interface Of Metal/ga 2 Omentioning
confidence: 99%
“…Huang et al showed that the asreceived rough β-Ga 2 O 3 crystal substrate with numerous scratches and pits found on the surface can be polished to the damage-free and smooth surface with the Rq surface roughness of 0.21 nm when using silica sol as slurry during the CMP process 5 . Xu et al also demonstrated that the root-mean-square (RMS) surface roughness of β-Ga 2 O 3 thin film deposited on the SiC substrate can be reduced from 5.43 nm to 0.8 nm after CMP process 7 . On the other hand, Ohira et al proposed that an atomically smooth β-Ga 2 O 3 surface with the uniform step-terrace structures can be obtained after the annealing at 1100 for 3 h 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The ion-cutting technique is compatible with wafer bonding and ion implantation equipment, and it has been used in the industrial application of SOI wafers, which is currently the most suitable heterogeneous integration technology for mass production of heterogeneous integration β-Ga 2 O 3 wafers. 10,11 In our previous work, the thermal transport properties of Ga 2 O 3 −Al 2 O 3 −SiC (GaOISiC) with an intermediate Al 2 O 3 amorphous layer with a thickness of 20 nm were investigated by using transient thermoreflectance (TTR) measurement. 12 The thermal transport properties in β-Ga integration materials (HIMs) are mainly influenced by the thermal conductivity of β-Ga 2 O 3 thin films (κ GaO ), heterogeneous host substrate, and effective thermal boundary resistance of the interface layer (TBR eff ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…If the defects and twin problems caused by the lattice/thermal mismatch between β-Ga 2 O 3 and any highly thermally conductive substrate can be overcome, then it will greatly subvert the market of β-Ga 2 O 3 power devices. The ion-cutting technique is compatible with wafer bonding and ion implantation equipment, and it has been used in the industrial application of SOI wafers, which is currently the most suitable heterogeneous integration technology for mass production of heterogeneous integration β-Ga 2 O 3 wafers. , …”
Section: Introductionmentioning
confidence: 99%